Simbol Semiotik dalam Novel Anomie Karya Rilda A. Oe. Taneko - Erwin Wibowo (JENTERA: Jurnal Kajian Sastra, 2017)
The aim of the research is to describe semiotic meanings in the Rilda A.Oe. Taneko’s novel, Anomie. The method used is decriptive method with semiotic approach by Pierce which includes icons, indexes, and symbols. The data source used in this research is the novel Anomie written by Rilda A.Oe. Taneko by investigating the data of symbols reflected in the quotations, and some books which are treated as references in this research. The collecting data technique is conducted by using literary review. The problems which are elaborated in this research are 1)identifying icons, indexes, and symbols semiotic in the novel Anomie written by Rilda A.Oe. Taneko, 2) describing icons, indexes, and symbols semiotic in the Rilda A.Oe. Taneko’s novel, Anomie. The results of this study show the novel Anomie by Rilda A.Oe. Taneko there is a semiotic symbol that includes the icon of educational institutions, social institutions, and entertainment venues. This novel index belongs to the strength, greed, pride and character figures. The symbols of this novel include symbols of wealth, sacrificial symbols, and symbols of love.AbstrakPenelitian ini bertujuan untuk mendeskripsikan makna semiotik yang terdapat dalam novel Anomie karya Rilda A.Oe. Taneko. Metode yang digunakan adalah metode deskriptif, dengan pendekatan semiotic Pierce yang meliputi ikon, indeks dan simbol. Sumber data yang dipakai dalam penelitian ini adalah novel Anomie karya Rilda A.Oe. Taneko dengan mengamati data-data ikon, indeks dan simbol yang tercermin dalam kutipan-kutipan tersebut, dan beberapa buku yang dijadikan referensi dalam penelitian ini. Teknik pengambilan data menggunakan teknik studi pustaka. Permasalahan yang akan dipecahkan dalam penelitian ini adalah (1) mengidentifikasi ikon, indeks dan simbol semiotik yang terdapat dalam novel Anomie karya Rilda A.Oe. Taneko, dan (2) mendeskripsikan ikon, indeks dan simbol semiotik yang terdapat dalam novel Anomie karya Rilda A.Oe. Taneko. Hasil penelitian ini menunjukan bahwa novel Anomie karya Rilda A.Oe. Taneko terdapat simbol semiotik yang meliputi ikon berupa lembaga pendidikan, lembaga sosial, dan tempat hiburan. Indeks dalam novel ini berupa kekuasaan, keserakahan, kesombongan dan kekhawatiran tokoh-tokohnya. Simbol pada novel ini meliputi simbol kekayaan, simbol pengorbanan, dan simbol cinta kasih.